A PREEMPTIVE REGIMEN REDUCED NOCICEPTIVE C-FOS EXPRESSION IN THE SOMATOSENSORY CORTEX OF SURGICAL PAIN PARADIGM. - Mumtaz , Saima; Najma Baseer; Syed Hamid Habib; Saleem, Saima; Malik, Sana (Journal of Ayub Medical College Abbottabad, 2026)
Background: Preemptive analgesia effectively diminishes postsurgical pain with fewer side effects, although its effectiveness and mechanism of action to reduced pain is still debatable. This study assessed the effectiveness of the preemptive regime in terms of neuronal c-fos expression on the somatosensory cerebral cortex (pain perception area of the spinothalamic tract) in both somatic and visceral pain models. Methods: Lab-base experimental investigation was carried out for almost two years (January 2022 to December 2023) at Khyber Medical University Peshawar. Eight to ten weeks old, eighteen Sprague-Dawley rats weighing between 150 and 250g were divided into: a) Somatic (skin incision only) (SG; n = 9); b) Visceral pain groups (uterine incision was given and then closed) (DG; n = 9). Each group was further categorised into Buprenorphine, Tramadol, and Saline subgroups; in addition, 2% lidocaine (7 mg/kg) was given along with preemptive analgesia preoperatively under general anaesthesia (isoflurane). c-fos mean cell count (MCC) and optical density (OD) were calculated on immunohistochemical slides two hours postoperatively. Data was analysed using MS Excel, SSPS version 25, Graph Pad Prism, and the Fiji Image J analyser. Results: In comparison to the saline group, buprenorphine and tramadol were significantly more effective in reducing the mean cell count and optical density of c-fos-expressing neuronal cells in the cortex (p ‰¤ 0.05) in both the somatic and visceral pain groups [superficial (somatic) and deep (visceral/uterine) surgical pain models]. Conclusion: The study concluded that a sufficient preemptive regimen is a practical way to avoid post-operative discomfort and pain following a surgical procedure.